Guests' acceptance of robotic services in Kuching park hotel, Sarawak / Nurul Anis Anil Aziz ... [et al.] - Anil Aziz, Nurul Anis; Adnan, Nur Arishah; Jamal, Salamiah A; Abdul Aziz, Azdel (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study investigates the factors influencing guests' acceptance of robotic services at the Kuching Park Hotel in Sarawak, highlighting the integration of technology in hospitality settings. The primary aim is to assess guests' perceptions and the effectiveness of robotic services in enhancing the guest experience. The study used a quantitative research design, collecting data from approximately 112 respondents through structured questionnaires. The analysis aims to comprehend guests' attitudes, satisfaction levels, and reservations about robotic services. The findings reveal significant insights into the acceptance levels of robotic services among hotel guests, identifying key drivers and barriers to adoption. The study contributes to academic and practical understanding by offering evidence-based recommendations for hoteliers considering implementing robotic services to improve guest experiences and operational efficiency. The implications of this research extend beyond the specific context of Kuching Park Hotel, offering valuable insights for the broader hospitality industry as it navigates technology integration into service delivery.